Music therapy and parent-infant bonding - Edwards, Jane, music therapist (Oxford : Oxford University Press, 2011)
'Music Therapy and Parent-Infant Bonding' is the first title in the field of music therapy to explore the contribution that music therapy can make in the very early years, for instance in situations regarding adopted children, or in ameliorating the effects of maternal depression on the mother-infant relationship.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Music therapy; Parent and infant